Analysis of the Application of the Hirarc Method (Hazard Identification Risk Assessment and Risk Control) in Potential Hazard Identification Activities in the Healthy Stevia Sugar Making Process at PT Tri Arga Makmur Sentosa - Sulandari, Uci; Winda Lestari, Putri; Mumpuni Ngesti Rahaju, Sri; Dewi Dyah Maharani, Maya; Basri, Hasan; Munawir, Abdillah; Istoni, Reza; Sugiyanto, Didik (Universitas Ibn Khaldun Bogor, 2024)
The still high level of work accidents requires companies to implement work safety and health programs to prevent work accidents. HIRADC (Hazard Identification, Risk Assessment, And Determining Control) is one of the K3 programs which consists of a series of activities to identify potential hazards and risks and provide appropriate control efforts according to the level of hazard risk. Based on the results of determining the risk level, there are 7 process activities with 2 types of risk. In each process activity, 5 (71%) hazard risks are included in the moderate category, and 2 (29%) hazard risks are included in the acceptable category.